Vegetation cover and microspatial distribution of sand flies (Diptera: Psychodidae) in an endemic locality for cutaneous leishmaniasis in Northern Argentina - Chanampa, Mariana del Milagro (2018)
The sand fly fauna in Hipólito Yrigoyen, Argentina, a locality where cutaneous leishmaniasis cases occur, was surveyed with zones of higher abundance of sand flies correlated to vegetation cover estimated through normalized difference vegetation index (NDVI). Sand flies were collected with 10 CDC traps during six nights, from December 2009 to January 2010. A map was built of expected sand flies abundance in which levels of NDVI were categorized. In total, 1,392 Phlebotominae (Diptera: Psychodidae) specimens were collected, comprised of the following species: Nyssomyia neivai (Pinto 1926), Migonemyia migonei (França 1920), species of the cortelezzii complex (Brèthes 1923), Evandromyia sallesi (Galvão & Coutinho 1940), and Psathyromyia shannoni (Dyar 1929). Positive correlations were found between the abundance of sand flies and the NDVI (P < 0.05) for buffer areas of < 150 m radii from the trap location points, i.e., the sand fly abundance was greater where vegetation cover and density were greater. In this context, plant cover should be taken into account to prioritize surveillance and control areas within the program of sand flies control in northern Argentina.